2016
DOI: 10.1021/acs.jpca.6b01235
|View full text |Cite
|
Sign up to set email alerts
|

Aun (n = 1,11) Clusters Interacting With Lone-Pair Ligands

Abstract: We analyze the pattern of binding energies (BEs) of small Aun clusters (n = 1-7, 11) with lone-pair ligands (L = H2O, SH2, NH3, PH3, PF3, PCl3, and PMe3) employing the density functional theory. We use PBE0 functional with the dispersion correction and scalar relativistic effective core potential. This approach provides correct BEs when compared with benchmark CCSD(T) calculations for Au-L and Au2-L complexes. The pattern of BEs of Aun-L complexes is irregular with BE for Au3 ≈ Au4 > Au2 > Au7 > Au5 > Au11 > A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
(174 reference statements)
0
18
0
Order By: Relevance
“…In Table 1, comparison is made with additional density functionals, including M06, 49 a double-hybrid functional (B2PLYP 50 ), a range-separation functional (CAM-B3LYP 51 ) and a meta-GGA functional (TPSSh 52,53 ); some of them were found to be reliable for gold-ligand interactions in previous benchmark calculations for smaller systems. 28,29 Results here suggest that PBE and PBE-GD3 are the most reliable for the systems of interest here. Moreover, with these two functionals, using a substantially smaller basis set (Lanl2dz for Au and 6-31G(d) for main group elements) does not lead to much larger errors.…”
Section: Qm Cluster Modelsmentioning
confidence: 74%
See 1 more Smart Citation
“…In Table 1, comparison is made with additional density functionals, including M06, 49 a double-hybrid functional (B2PLYP 50 ), a range-separation functional (CAM-B3LYP 51 ) and a meta-GGA functional (TPSSh 52,53 ); some of them were found to be reliable for gold-ligand interactions in previous benchmark calculations for smaller systems. 28,29 Results here suggest that PBE and PBE-GD3 are the most reliable for the systems of interest here. Moreover, with these two functionals, using a substantially smaller basis set (Lanl2dz for Au and 6-31G(d) for main group elements) does not lead to much larger errors.…”
Section: Qm Cluster Modelsmentioning
confidence: 74%
“…below); previous benchmark studies28,29 that focused on smaller Au-ligand systems found that PBE-GD3 and TPSSh are among the best functionals compared to CCSD(T) calcu-…”
mentioning
confidence: 95%
“…This charge-flow tendency, from organic molecules to metallic surfaces, is also consistent with previous reports. 67,68 The nature of Au–PPX bond is basically analogous to that of gold clusters interacting with lone-pair ligands 69 and mostly dominated by a σ bond with the distribution of unshared electrons in the HOMO of PPX molecule and the LUMO of gold clusters. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the interaction of Ag 2 with cysteine in the gas phase, its contribution to the final binding energy is computed to be ∼1.5 kcal/mol, which lies within the expected uncertainty of up-to-date DFT calculations, being ±3.0 kcal/mol. The previous investigation 40 on the lone-pair affinity of small gold clusters also confirmed that the BSSE uncorrected results tend to correlate with the benchmark data better than the corrected ones because of error mutual cancellations. To include the influences of the biological environment, we employ the integral equation formalism-polarizable continuum model (IEF-PCM) 41 for treating the systems considered in aqueous solution.…”
Section: ■ Computational Methodsmentioning
confidence: 99%